1998
DOI: 10.1093/oxfordjournals.pcp.a029294
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Membrane Lesions Induced by a Freeze-Thaw Cycle in Protoplasts Isolated from Deacclimated Tubers of Jerusalem Artichoke (Helianthus tuberosus L.)

Abstract: The processes of freezing injury in Jerusalem artichoke (Helianthus tuberosus L.) tubers were studied using protoplasts isolated from cold-acclimated and deacclimated tubers. Prior to freezing, protoplasts were preloaded with 10 microM fluorescein diacetate (FDA) in an isotonic sorbitol solution. After freeze-thawing at various temperatures, cell viability was evaluated under a fluorescence microscope. In cold-acclimated tubers, more than 80% of protoplasts survived freezing to -20 degrees C. By contrast, in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In cereals, the plasma membrane is the membrane most vulnerable to this kind of damage; other membranes are also aected but often at a lower temperature. However , in other species and organs, damage to the tonoplast limits survival (Stout et al, 1980;Zhang and Willison, 1992b;Murai and Yoshida, 1998).…”
Section: Freezing-induced Cellular Dehydration and Damagementioning
confidence: 99%
“…In cereals, the plasma membrane is the membrane most vulnerable to this kind of damage; other membranes are also aected but often at a lower temperature. However , in other species and organs, damage to the tonoplast limits survival (Stout et al, 1980;Zhang and Willison, 1992b;Murai and Yoshida, 1998).…”
Section: Freezing-induced Cellular Dehydration and Damagementioning
confidence: 99%
“…For the measurement of the cytoplasmic pH by pH-ratiometry, it is critically important to load the fluorophore specifically into the cytoplasm (Yoshida 1994). For this purpose, protoplasts are more suitable than tissue sections because of the specific localization of the fluorophore in the cytoplasm after loading of the fluorophore under specified conditions (Murai and Yoshida 1998a).…”
Section: Measurements Of Cytoplasmic Ph During Freezingmentioning
confidence: 99%
“…These results indicate that the pH reduction lower than 6.5 in non-acclimated protoplasts is probably due to a release of H+ ions across the vacuolar membrane, apparently suggesting the role of the lesions associated with the vacuolar membrane in cell injury. In fact, we have recently suggested that the decrease in freezing tolerance of protoplasts isolated from Jerusalem artichoke tuber after deacclimation is mainly due to destabilization of the vacuolar membrane (Murai and Yoshida 1998a).…”
Section: Physiological Significance Of Freeze-induced Ph Changesmentioning
confidence: 99%
“…They include: water content, both absolute and relative (e.g. Berjak et al 1992; Sun et al 1994; Farrant 2000), water potential and related functions such as water activity (Roberts and Ellis 1989; Vertucci and Roos 1990; Tompsett and Pritchard 1993), cell volume (Merryman 1974; Steponkus 1979; Murai and Yoshida 1998), intracellular viscosity (Vertucci and Roos 1990; Koster 1991; Williams et al 1993; Leopold et al 1994; Buitink et al 1998; Leprince and Hoekstra 1998; Bryant et al 2001), intermolecular proximity (Lis et al 1982; Steponkus et al 1995) and structural water (Ladbrooke and Chapman 1969; Vertucci and Leopold 1984; Crowe et al 1990).…”
mentioning
confidence: 99%